Methods to modify supersaturation rate in membrane distillation crystallisation: control of nucleation and crystal growth kinetics (including scaling) - Ouda, Alaa Samir; Bajón Fernández, Yadira; McAdam, Ewan (Cranfield University, 2023)
The attached Excel dataset consists of figure and table data used in this chapter. Each figure/table is placed in a separate Excel sheet while the formatting of the figures was consistent with a Word file.
Keywords: brine management'; 'resource recovery'; 'crystal growth'; 'hollow fibre'; 'direct contact'